СONSTRUCTION OF COGNITIVE-DISCURSIVE MODEL OF DIACHRONIC PLURALITY IN TRANSLATION AS INTERPRETATIVE-HEURISTIC ACTIVITY - Yana V. Boiko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
Cognitive-discursive modelling is an effective research methodology since, in the translation process, the translator himself uses target language means to model the reality described by the author. Also, an important factor in the translation process modelling is the analysis and comparison of chronologically distant original work’s various retranslations, which allows us to follow the influence of discursive and cognitive factors on the process and result of translation. The purpose of the article is to justify the complex methodology of cognitive-discursive model construction (hereinafter the CDM) of the diachronic plurality in chronologically distant original work translations as an interpretive and heuristic activity. The tasks of the research are the following: to construct the CDM discursive module; to construct the CDM cognitive module; to structure the CDM retranslation module. The material of the study is connotative original units, chosen from chronologically distant original text – W. Shakespeare’s tragedy Othello (1604) – and their equivalents in Ukrainian diachronic retranslations performed by P. Kulish (1819–1897), I. Steshenko (1898–1987), and O. Gryaznov (1940–2021). Taking into account translation studies interdisciplinary nature, the methodology of the CDM complex construction procedure is determined by a polyparadigmatic approach that combines discursive, linguistic, cognitive, and translation directions of analysis. Each of these directions is represented by a number of methods, techniques and analysis procedures. As an interpretive-heuristic activity, the CDM construction algorithm involves three stages: the construction of the CDM discursive module by applying discourse analysis methodology, which involves the segmentation of the discursive module into three components: extralingual, textual and lingual; construction of the CDM cognitive module by applying cognitive linguistics methodology, in particular the method of frame mapping, as well as the application of cognitive analysis, comparative analysis, conceptual analysis and frame modelling; construction of the CDM retranslation module by applying the methodology of translation studies, in particular contrastive-translational analysis and transformational analysis. Conclusion. The combination of discursive, cognitive and retranslation modules contributes to a deeper understanding of the artistic text and the degree of the author’s worldview representation in the translation. The CDM construction of the diachronic plurality of chronologically distant original work translations makes it possible to study a number of problems comprehensively, namely: developing criteria for translation adequacy, revealing the causes of obstacles on the way to achieve an adequate translation, and determining ways of their maximum reduction and/or elimination in the translation process.